Practical NMR spectroscopy laboratory guide : using Bruker spectrometers - Harwood, John S.; Mo, Huaping (San Diego, CA : Academic Press, an imprint of Elsevie, 2016)
Practical NMR Spectroscopy Laboratory Guide is designed to provide non-expert NMR users, typically graduate students in chemistry, an introduction to various facets of practical solution-state NMR spectroscopy. Each chapter offers a series of hands-on exercises, introducing various NMR concepts and experiments and guiding the reader in running these experiments using an NMR spectrometer. The book is written for use with a Bruker NMR spectrometer running TopSpin software versions 1 or 2. This practical resource functions both as a text for instructors of a practical NMR course and also as a reference for spectrometer administrators or NMR facility directors when doing user training. This guide serves as serve as excellent, practical resource on its own or as a companion book to Timothy Claridge's High-Resolution NMR Techniques in Organic Chemistry, 2nd Edition (Elsevier, 2009).
Online resource; title from PDF title page (EBSCO, viewed November 5, 2015).
Keywords: Nuclear magnetic resonance spectroscopy -- Handbooks, manuals, etc; Nuclear magnetic resonance spectroscopy -- Laboratory manuals; SCIENCE / Chemistry / Analytic; Nuclear magnetic resonance spectroscopy; Electronic books; Handbooks and manuals; Laboratory manuals